Clinical Relevance of lncRNA and Mitochondrial Targeted Antioxidants as Therapeutic Options in Regulating Oxidative Stress and Mitochondrial Function in Vascular Complications of Diabetes - Tarun Pant; Nnamdi Uche; Matea Juric; Zeljko J. Bosnjak (MDPI AG, 2023)
Metabolic imbalances and persistent hyperglycemia are widely recognized as driving forces for augmented cytosolic and mitochondrial reactive oxygen species (ROS) in diabetes mellitus (DM), fostering the development of vascular complications such as diabetic nephropathy, diabetic cardiomyopathy, diabetic neuropathy, and diabetic retinopathy. Therefore, specific therapeutic approaches capable of modulating oxidative milieu may provide a preventative and/or therapeutic benefit against the development of cardiovascular complications in diabetes patients. Recent studies have demonstrated epigenetic alterations in circulating and tissue-specific long non-coding RNA (lncRNA) signatures in vascular complications of DM regulating mitochondrial function under oxidative stress. Intriguingly, over the past decade mitochondria-targeted antioxidants (MTAs) have emerged as a promising therapeutic option for managing oxidative stress-induced diseases. Here, we review the present status of lncRNA as a diagnostic biomarker and potential regulator of oxidative stress in vascular complications of DM. We also discuss the recent advances in using MTAs in different animal models and clinical trials. We summarize the prospects and challenges for the use of MTAs in treating vascular diseases and their application in translation medicine, which may be beneficial in MTA drug design development, and their application in translational medicine.